Cardiac Outcomes After Ischemic Stroke or Transient Ischemic Attack: Effects of Pioglitazone in Patients With Insulin Resistance Without Diabetes Mellitus. Issue 20 (16th May 2017) - Young, Lawrence H.; Viscoli, Catherine M.; Curtis, Jeptha P.; Inzucchi, Silvio E.; Schwartz, Gregory G.; Lovejoy, Anne M.; Furie, Karen L.; Gorman, Mark J.; Conwit, Robin; Abbott, J. Dawn; Jacoby, Daniel L.; Kolansky, Daniel M.; et al.
Abstract : Background: Insulin resistance is highly prevalent among patients with atherosclerosis and is associated with an increased risk for myocardial infarction (MI) and stroke. The IRIS trial (Insulin Resistance Intervention after Stroke) demonstrated that pioglitazone decreased the composite risk for fatal or nonfatal stroke and MI in patients with insulin resistance without diabetes mellitus, after a recent ischemic stroke or transient ischemic attack. The type and severity of cardiac events in this population and the impact of pioglitazone on these events have not been described. Methods: We performed a secondary analysis of the effects of pioglitazone, in comparison with placebo, on acute coronary syndromes (MI and unstable angina) among IRIS participants. All potential acute coronary syndrome episodes were adjudicated in a blinded fashion by an independent clinical events committee. Results: The study cohort was composed of 3876 IRIS participants, mean age 63 years, 65% male, 89% white race, and 12% with a history of coronary artery disease. Over a median follow-up of 4.8 years, there were 225 acute coronary syndrome events, including 141 MIs and 84 episodes of unstable angina. The MIs included 28 (19%) with ST-segment elevation. The majority of MIs were type 1 (94, 65%), followed by type 2 (45, 32%). Serum troponin was 10× to 100× upper limit of normal in 49 (35%) and >100× upper limit of normal in 39 (28%). Pioglitazone reduced the risk of acute coronary syndrome (hazard ratio, 0.71; 95% confidence interval, 0.54–0.94; P =0.02). Pioglitazone also reduced the risk of type 1 MI (hazard ratio, 0.62; 95% confidence interval, 0.40–0.96; log-rank P =0.03), but not type 2 MI (hazard ratio, 1.05; 95% confidence interval, 0.58–1.91; P =0.87). Similarly, pioglitazone reduced the risk of large MIs with serum troponin >100× upper limit of normal (hazard ratio, 0.44; 95% confidence interval, 0.22–0.87; P =0.02), but not smaller MIs. Conclusions: Among patients with insulin resistance without diabetes mellitus, pioglitazone reduced the risk for acute coronary syndromes after a recent cerebrovascular event. Pioglitazone appeared to have its most prominent effect in preventing spontaneous type 1 MIs. Clinical Trial Registration: URL:http://clinicaltrials.gov . Unique identifier: NCT00091949. Abstract : Supplemental Digital Content is available in the text.